Incidence of residual stresses and steel properties variability on corroded bulk carrier reliability. (1st December 2016) - Campanile, A.; Piscopo, V.; Scamardella, A.
Abstract: Time-variant sagging/hogging hull girder bending capacity of a corroded bulk carrier is determined by Monte Carlo simulation, in terms of mean values, variation coefficients and probability density functions; the incidence of welding residual stresses and steel mechanical properties is purposely investigated. Time-variant hull girder reliability is characterized, for both sagging and hogging conditions, by the annual failure probability and is determined by Second-Order Reliability Method. Sensitivity coefficients of all random variables at discrete points in time are also determined. Four different scenarios are considered and analysed, in order to separately and jointly investigate the incidence of welding residual stresses and material properties variability on hull girder capacity and annual failure probability and compare individual results with the reference case, which is relative to no welding stresses and material properties nominal values. The Capesize single side bulk-carrier, benchmarked in the last ISSC Report, is assumed as test case. Finally, obtained results of time-variant hull girder statistical properties and annual failure probabilities are discussed. Highlights: Time-variant bulk carrier ultimate strength capacity. Time-variant corrosion wastage. Welding residual stresses and steel properties variability. Monte Carlo simulation. Second-Order Reliability Analysis.